Effect of surfactants on the biofilm of Rhodococcus erythropolis, a potent degrader of aromatic pollutants - Schreiberová, Olga; Hedbávná, Petra; Cejková, Alena; Jirků, Vladimír; Masák, Jan (New biotechnology, 2012)
Bioremediation processes based on biofilms are usually very effective. The presence of (bio)surfactants in such processes can increase bioavailability of hydrophobic pollutants in aqueous phase. However, surfactants can affect the biofilm as well as individual microbial cells in different ways. Biosurfactants produced by a microbial population can be involved in the final structure of biofilm. An external application of synthetic surfactants or 'foreign' biosurfactants often results in partial or complete destruction of the biofilm and their high concentrations also have a toxic effect on microbial cells. Finding a suitable surfactant and its concentration, which would minimize the negative effects mentioned above, would allow to construct effective bioremediation processes using the benefits of both the biofilm and the surfactant. In this context, G(+) bacterium Rhodococcus erythropolis, which has a wide potential for biodegradation of aromatic compounds, was studied. High surface hydrophobicity of its cells, given mainly by the presence of mycolic acids in the cell envelopes, allows formation of stable biofilms. Three synthetic surfactants (Spolapon AOS 146, Novanik 0633A, Tween 80) and rhamnolipid isolated from Pseudomonas aeruginosa were used. Changes in initial adhesion and biofilm formation caused by the surfactants were monitored in a flow cell equipped with hydrophilic/hydrophobic carriers and analyzed by image analysis.
Keywords: Colony Count, Microbial; aromatické uhlovodíky; Batch Cell Culture Techniques; Environmental Pollutants; Phenols; biofilmy; micely; Rhodococcus; techniky vsádkové kultivace; povrchově aktivní látky; fenoly; Biofilms; Biodegradation, Environmental; látky znečišťující životní prostředí; Hydrocarbons, Aromatic; biodegradace; Surface-Active Agents; hydrofobní a hydrofilní interakce; Hydrophobic and Hydrophilic Interactions; Rheology; Polyethylene; Micelles; reologie; počet mikrobiálních kolonií; polyethylen